(untitled) (The Pakistan Development Review, 1995)
Development economics seeks to isolate the elemental forces at work in developing countries that raise per capita income, initially and then continuously, by exploiting fully the inter-industry and inter-sectoral network of economies of scale, externalities, and complementarities; it also analyses the key factors that decide a fair distribution of the fruits of economic progress, and those which enhance human happiness more directly. The process of economic development is seen as complex, even mysterious; which must be tackled by conscious planning where coordination failures are threatening, and through the market mechanism if information problems are daunting. Yet a persistent theme in economic literature has been one of denial of the (marginal) utility of development economics. Essentially, most of these “arguments” against development economics are nothing more than a thinly disguised championing of the ideology of free-market capitalism and neo-classical economics as the ultimate truths about the economic universe [Heilbroner (1990)]. They are a frame of thought into which development economics would not fit “naturally”. As one would expect, these views about development economics have not gone unchallenged. But the main issue is far from settled. I, therefore, restate here the case for development economics to make sure that development policy is saved from the revages of an incompatible liberalist philosophy. I would concentrate on issues related to the acknowledged mainsprings of economic progress, and those related to the relationship between trade and growth and the interface of the government and the market. Finally, I would like to emphasise the need to acquire an overarching ethical vision in order to identify the ends of economic progress and to order the means to achieve them.